Model-independent measurement of the excited fraction in a magneto-optical trap(MOT) - Shah, Mudessar H. (Kansas State University, 2006)
In many experiments involving a magneto-optical trap (MOT) it is of great importance to know the fraction of atoms left in an excited state due to the trapping process. Generally speaking, researchers have had to use overly simplistic and untested models to estimate this fraction. In this work, the excited fraction of 87Rb atoms in a MOT is measured using a model-free approach. A simple model is fit to the fractions which were obtained for a range of MOT parameters. Using the results of this work, the excited fraction of 87Rb atoms trapped in a MOT can be accurately estimated with knowledge of only the trapping laser intensity and detuning. The results are only weakly dependent on other MOT parameters.
Keywords: Excited fraction; Laser cooling of atoms; Physics, Atomic (0748); Physics, Molecular (0609); Physics, Optics (0752)